Dari Sosialisme menuju Islam Makrifat: Evolusi Pemikiran HOS Tjokroaminotoaminoto, 1924 – 1928 - Miftakhus Sifa' Bahrul Ulumiyah (Nalar: Jurnal Peradaban dan Pemikiran Islam)
This piece of writing delves into the evolution of HOS Tjokroaminotos ideas between 1924 and 1928. HOS Tjokroaminoto is famously associated with the concept of Islamic Socialism, which he first wrote about in his well-known work Islam and Socialism in 1924. However, his ideas did not remain stagnant and in 1928, he wrote a mystical work called Inspecting the Nature of Truth, which was reviewed by only a few people. This study adopts a historical research method with an intellectual history approach and uses Hans-George Gadamers theory as a tool to analyse the texts and thought contexts. The article suggests that HOS Tjokroaminotos thinking went through three phases during the period 1924-1928: the Islamic socialism phase in 1924, the search phase in 1927, and the pinnacle phase of thought in 1928, which resulted in his most famous work. The evolution of his thinking was influenced by both internal and external factors. This pinnacle work can serve as a point of reference for understanding the trajectory of HOS Tjokroaminotos thought throughout his life and in all his works.